Impact of Inactive Empiric Antimicrobial Therapy on Inpatient Mortality and Length of Stay - Scarsi, Kimberly K. (American Society for Microbiology, 2006)
The consequences of inactive empiric antimicrobial therapy are not well-described and may cause prolonged hospitalization or infection-related mortality. In vitro susceptibility results for 884 patients hospitalized at an academic medical center with gram-negative bloodstream infections (GNBI) from 2001 to 2003 were matched to antimicrobial orders within 24 h of culture. Clinical characteristics, organism, inpatient mortality, and length of stay after culture for patients with GNBI were compared between patients receiving active versus inactive empiric antimicrobial therapy. A total of 14.1% of patients with GNBI received inactive empiric therapy, defined as no antimicrobial therapy within 24 h of the culture active against the identified organism based on in vitro microbiology reports. Patients who received inactive therapy were more likely to be younger, to be infected with Pseudomonas aeruginosa, to have a nosocomial infection, and to receive antimicrobial monotherapy but less likely to be bacteremic with Escherichia coli or to have sepsis (P < 0.05). There were no significant differences in mortality between patients receiving active versus inactive empiric therapy (16.1% versus 13.6%, respectively) or in length of stay after positive culture (11.5 days versus 12.6 days, respectively). Only 45 patients had greater than 2 days of exposure to inactive therapy; however, 8/30 patients (26.7%) who never received active antimicrobial therapy died while in the hospital. Inactive empiric therapy was more common in healthier patients. Inactive antimicrobial therapy in the first 24 h did not significantly impact average outcomes for GNBI among hospitalized patients but may have caused harm to specific individuals.